Single particle tunneling spectrum of superconducting Nd1-xSrxNiO2 thin films - Qiangqiang Gu (Nature Portfolio, 2020)
The recent observation of superconductivity in nickelate thin films has attracted a lot of attentions. Here, authors report single particle tunneling spectra on the superconducting nickelate thin films revealing two types of gap feature with one V-shape and the other a full gap.